Super-resolution photoacoustic microscopy using photonic nanojets : a simulation study - Wen, Zhuo-Bin (2014)
Optical resolution photoacoustic microscopy (ORPAM) is important for various biomedical applications, such as the study of cellular structures, microcirculation systems, and tumor angiogenesis. However, the lateral resolution of a conventional ORPAM is limited by optical diffraction. In this work, we report a simulation study to achieve subdiffraction-limited super-resolution in ORPAM using microspheres. Laser radiation is focused through a microsphere to generate a photonic nanojet, which provides the possibility to break the diffraction limit in ORPAM by reducing the size of the excitation volume. In our simulations using microspheres, we observed improvement in the lateral resolution up to ∼fourfold compared to conventional ORPAM. The method is simple, cost effective, and can provide far-field resolution. This approach may provide new opportunities for many biomedical imaging applications that require finer resolution.